Early childhood health during conflict: The legacy of the Lord's Resistance Army in Northern Uganda - Sarah Bridges; Douglas Scott (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
This study finds evidence of irreversible health deficits amongst young children who were exposed to the Lord's Resistance Army insurgency in Northern Uganda (1987- 2007). The causal effect of the conflict is found to be a 0.65 standard deviation fall in height-for-age z-scores amongst children exposed for a period of more than six months. In contrast, the health impacts of shorter periods of exposure are found to be relatively minimal. These findings highlight the need for a swift resolution to conflict, in particular where it impacts heavily upon civilian populations, without which, the health consequences of protracted wars may extend far beyond the current generation.
Keywords: I12; J13; O12; 330; Conflict; Uganda; Child health